2021
DOI: 10.1186/s12877-021-02579-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators for implementation of a complex health services intervention in long-term care homes: a qualitative study using focus groups

Abstract: Background With rising numbers of elderly people living in nursing homes in Germany, the need for on-site primary care is increasing. A lack of primary care in nursing homes can lead to unnecessary hospitalization, higher mortality, and morbidity in the elderly. The project CoCare (“coordinated medical care”) has therefore implemented a complex health intervention in nursing homes, using inter alia, regular medical rounds, a shared patient medical record and medication checks, with the aim of i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Previous reports demonstrated that local governments set standardized implementation rules and quantifiable assessment indicators, and service providers gave priority to completing assessment tasks, resulting in service shortages [ 32 , 35 ]. In other countries, such as Germany and Poland, caregivers have a disproportionate amount of time allocated to organizing documents, completing complex bureaucratic procedures, and providing services [ 68 , 69 ]. In addition, Chen and Zheng found that service providers tend to change service items frequently to meet the preferences of purchasers and local officials, which makes it difficult to provide detailed, sustainable and in-depth services [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that local governments set standardized implementation rules and quantifiable assessment indicators, and service providers gave priority to completing assessment tasks, resulting in service shortages [ 32 , 35 ]. In other countries, such as Germany and Poland, caregivers have a disproportionate amount of time allocated to organizing documents, completing complex bureaucratic procedures, and providing services [ 68 , 69 ]. In addition, Chen and Zheng found that service providers tend to change service items frequently to meet the preferences of purchasers and local officials, which makes it difficult to provide detailed, sustainable and in-depth services [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies highlighted the complexity of implementation processes in nursing homes, in and outside a pandemic situation [ 15 , 16 ]. Barriers and facilitators have also been described in the implementation of palliative care approaches in geriatric care [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eine erste Inventarisierung von Kooperationen zwischen Ärzteschaft und Pflegefachpersonal in Deutschland lieferte mögliche Ansatzpunkte für Verbesserungen [ 29 ]. Diese wurden in dem Projekt „CoCARE“ mittels regelmäßiger ärztlicher Visiten, einer gemeinsamen Patientenakte und Medikamentenkontrollen adressiert [ 30 ]. International empfiehlt die Weltgesundheitsorganisation (WHO) für eine fokussierte Kommunikation zwischen ärztlich und pflegerisch tätigen Personen im Gesundheitswesen das „Situation-Background-Assessment-Recommendation“ (SBAR)-Tool 2 [ 48 – 50 ].…”
Section: Diskussionunclassified